Surface plasmon inhibited photo-luminescence activation in CdSe/ZnS core–shell quantum dots. (11th May 2016) - Chen, Junsheng; Žídek, Karel; Abdellah, Mohamed; Al-Marri, Mohammed J; Zheng, Kaibo; Pullerits, Tõnu
Abstract: In a composite film of Cd x  Se y  Zn1− x  S1− y gradient core–shell quantum dots (QDs) and gold nanorods (NRs), the optical properties of the QDs are drastically affected by the plasmonic nanoparticles. We provide a careful study of the two-step formation of the film and its morphology. Subsequently we focus on QD luminescence photoactivation—a process induced by photochemical changes on the QD surface. We observe that even a sparse coverage of AuNRs can completely inhibit the photoactivation of the QDs' emission in the film. We demonstrate that the inhibition can be accounted for by a rapid energy transfer between QDs and AuNRs. Finally, we propose that the behavior of emission photoactivation can be used as a signature to distinguish between energy and electron transfer in the QD-based materials.